Non-Formal Education for MSMEs based on Business Financial Management Counseling - Santoso, Aprih; Widowati, Sri Yuni; Saefudin, Saefudin; Chamami, M Rikza (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2021)
Micro & small business in Tegalarum village is one of the micro & small business groups in Mranggen District, Demak Regency. The majority of these micro & small business entrepreneurs do not have skills in the field of finance, especially cash flow statements (cash flow statements). Therefore, non-formal education activities are needed in the form of counseling aimed at providing non-formal education through an outreach approach to the preparation of cash flow reports so that these reports can be accounted for and accountable. ) which has been prepared by the Indonesian Institute of Accountants (IAI) as a standard compiler for cash flow reports, so that this report can later be accounted for and can be read by parties with an interest in the report. The activity method in the form of a participatory training approach is carried out through several activity steps, namely: counseling, training and monitoring and evaluation. As for the results of non-formal education activities through counseling that has been carried out, it is known that micro & small business entrepreneurs in Tegalarum Village, Mranggen District, Demak Regency have been able to increase their knowledge and skills in making financial reports, especially cash flow reports.Usaha mikro & kecil  desa  Tegalarum merupakan salah satu kelompok Usaha mikro & kecil Kecamatan Mranggen Kabupaten Demak. Mayoritas pengusaha Usaha mikro & kecil tersebut belum mempunyai skill dibidang finance khususnya cash flow statement (laporan arus kas). Oleh karena itu, dibutuhkan kegiatan pendidikan non formal berupa penyuluhan yang  bertujuan memberikan pendidikan jon formal melalui pendekatan penyuluhan penyusunan laporan arus kas agar laporan tersebut  dapat dipertanggungjawabkan  dan akuntabel  Dalam  penyusunan  laporan    arus kas  tersebut telah  diatur dalam  Pedoman  Standar  Arus kas kuntansi  Keuangan  (PSAK-45)  yang  telah  disusun  oleh Ikatan Akuntan Indonesia (IAI) sebagai penyusun standar laporan arus kas, agar laporan ini nantinya bisa dipertanggungjawabkan dan dapat dibaca oleh pihak-pihak yang berkepentingan terhadap laporan tersebut. Metode kegiatan dalam bentuk pendekatan participatory training dilakukan melalui beberapa langkah kegiatan. yaitu : penyuluhan, pelatihan dan monitoring serta evaluasi.  Adapun hasil kegiatan pendidikan non formal mekalui penyuluhan yang telah dilaksanakan diketahui bahwa pengusaha Usaha mikro & kecil desa Tegalarum Kecamatan Mranggen Kabupaten Demak sudah mampu meningkatkan pengetahuan dan ketrampilan dalam membuat laporan keuangan khususnya laporan arus kas.